The effect of polyphenol to visceral fat profile protein at obesity model rat - Sri Rahayu Lestari; Nuning Wulandari; Siti Imroatul Maslikah (Biomedical Engineering, 2016)
Objective: To asses visceral fat profile protein between normal and obesity model rat. Material and Methods: Normal and obesity rat model have been treated with polyphenol from rambutan peel extract for 12 weeks. Rat were divided into 2 major group  based on their weight which normal rat and obesity model rat respectively have average weight 180-200 gram and 360-380 gram. This treatment were divided into minor group which are placebo (without treatment),  treatment with ellagic acid and treatment with polyphenol (dosage 15 mg/kg body weight; 30 mg/kg body weight and 60 mg/kg body weight. Rat were sacrificed after 12 weeks treatment to asses visceral fat profile protein and continue with running SDS PAGE12,5 %. Protein molecular weight sample were calculated with regression analysis between marker protein mobility and logarithm from marker. Band protein analysis were analyze qualitative with SDS PAGE meanwhile quantitative analysis with Gel Doc (Bio Rad). Density band protein were analyze were using Quantity One software and confirmed with Western Blotting.Result: Protein profile characteristic normal rat and obesity-model rat were in range between117-20 k Da. The amount of band protein were found in normal rat were less than the amount of protein at obesity-model rat. Conclusion: There were difference molecular weight at protein density 57 k Da for obesity model rat which has been treated with rambutan peel extract.